Quality improvement of rule-based gene group descriptions using information about GO terms importance occurring in premises of determined rules - Sikora, Marek; Gruca, Aleksandra (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we present a method for evaluating the importance of GO terms which compose multi-attribute rules. The rules are generated for the purpose of biological interpretation of gene groups. Each multi-attribute rule is a combination of GO terms and, based on relationships among them, one can obtain a functional description of gene groups. We present a method which allows evaluating the influence of a given GO term on the quality of a rule and the quality of a whole set of rules
Keywords: decision rules; importance of rules premises; measures of rules interestingness; gene ontology; descriptions of gene groups